(untitled) (Bangladesh Journal of Agricultural Research, 2020)
The experiment was conducted at the Seed Laboratory, Regional Agricultural Research Station, Bangladesh Agricultural Research Institute, Jamalpur in 2013 to study the effect of seed moisture content and storage containers on seed quality of soybean genotypes. Three genotypes of soybean (AGS 191, ASET 93 and Shohag), four initial seed moisture content (6, 8, 10 and 12%) and two types of storage containers (polythene bag and glass jar) were included in the experimental treatment. Seeds of soybean genotypes was stored at ambient condition were temperature ranged from 15.97 to 29.37 0C, relative humidity ranged from 75.21 to 86.23% and rainfall ranged from 0.00 to 425mm during the whole storage period. Seed moisture content (%), germination (%) and vigour index were recorded at 50, 100, 150 and 200 days after storage (DAS). Result showed that final seed moisture content increased with the increase of initial seed moisture content. Genotype AGS 191 showed the highest germination (%) and vigour index. Seeds stored in polythene bag or glass jar showed similar performance for germination (%) and vigour index. Highest seed moisture content significantly reduced the germination and vigour index errespective of containers. The results indicate that soybean seed can be stored safely for at least 200 days maintaining >80% germination and high vigour when stored in polythene bag or glass jar with 6-8% initial moisture content at ambient room temperature and relative humidity. Bangladesh J. Agril. Res. 44(4): 631-640, December 2019